2019
DOI: 10.1371/journal.pcbi.1007524
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a multi-level trophic organization of the human gut microbiome

Abstract: The human gut microbiome is a complex ecosystem, in which hundreds of microbial species and metabolites coexist, in part due to an extensive network of cross-feeding interactions. However, both the large-scale trophic organization of this ecosystem, and its effects on the underlying metabolic flow, remain unexplored. Here, using a simplified model, we provide quantitative support for a multi-level trophic organization of the human gut microbiome, where microbes consume and secrete metabolites in multiple itera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 42 publications
2
58
0
Order By: Relevance
“…Our approach uses the idea that we can leverage cross-feeding interactions -which comprise knowing the metabolites that each microbial species is capable of consuming and producing -to mechanistically connect the levels of microbes and metabolites in the human gut. Several different mechanistic models in past studies have shown that this is indeed possible 18,20,29,35,36 . While GutCP is generalizable and can be used with any of these models, in this manuscript, we use a previously published consumer-resource model 20 .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Our approach uses the idea that we can leverage cross-feeding interactions -which comprise knowing the metabolites that each microbial species is capable of consuming and producing -to mechanistically connect the levels of microbes and metabolites in the human gut. Several different mechanistic models in past studies have shown that this is indeed possible 18,20,29,35,36 . While GutCP is generalizable and can be used with any of these models, in this manuscript, we use a previously published consumer-resource model 20 .…”
Section: Resultsmentioning
confidence: 91%
“…GutCP combines machine learning techniques 33,34 with an ecological model of the microbiome. The ecological model is effective at bootstrapping previously-known direct interactions and estimating the metabolic environment of the gut in agreement with experimental measurements 20 . GutCP uses these estimates as a leverage to predict new cross-feeding interactions.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Universal building block interactions could be used to build purpose-built predictive dynamic models in an "n of one" manner, meaning built with data from a single patient [9,10]. It is as yet an open question as to the nature of these building blocks, and indeed if any can be found [11,12,13,14,15]. Here, we examine two popular modeling frameworks, species-species interaction (SSI) and species-metabolite interaction (SMI) models, and evaluate them using interdependent growth experiments of single species, pairs, and trios from Friedman et al [16].…”
mentioning
confidence: 99%